2001
DOI: 10.1183/09031936.01.00097301
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators in nasal lavage, induced sputum and serum of employees with rheumatic and respiratory disorders

Abstract: Inflammatory mediators in nasal lavage, induced sputum and serum of employees with rheumatic and respiratory disorders. M. Roponen, J. Kiviranta, M. Seuri, H. Tukiainen, R. Myllykangas-Luosujärvi, M-R. Hirvonen. #ERS Journals Ltd 2001. ABSTRACT: Exposure to microbes present in mould-damaged buildings has been linked to increased frequency of various inflammatory diseases. The current study examined differences in inflammatory mediators in nasal lavage (NAL), induced sputum (IS) and serum of occupants with rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…After exclusion of the asthmatic subject, there was no difference in FEV1 decrease between the challenges. This is in line with a previous study where no significant differences in lung functions were found between occupants with respiratory or rheumatic disorders and their controls, all working in the same moisture-damaged building [5]. Conversely, in this study, the baseline FVC and FEV1 were significantly lower among the mould-exposed subjects when compared with their controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After exclusion of the asthmatic subject, there was no difference in FEV1 decrease between the challenges. This is in line with a previous study where no significant differences in lung functions were found between occupants with respiratory or rheumatic disorders and their controls, all working in the same moisture-damaged building [5]. Conversely, in this study, the baseline FVC and FEV1 were significantly lower among the mould-exposed subjects when compared with their controls.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is also supported by previous studies pointing out that subjects exposed to indoor air microbes more frequently report airway symptoms than their control counterparts [5,24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Exhaled NO levels were significantly elevated in children living in homes with average FA levels ≥ 50 ppb (Franklin et al, 2000). Moreover, employees with respiratory symptoms had markedly higher exhaled NO values (Roponen et al, 2001). These results suggested that VOCs could increase the activity of NOS.…”
Section: Introductionmentioning
confidence: 54%
“…For HDMs, sensitization limit of 100 mites/g has been suggested (Platts-Mills et al 1989), but no corresponding value for SMs has been published. A high prevalence of positive skin prick test (SPT) results for SM allergens has been reported in symptomatic employees working in a moisture-damaged building (Roponen et al 2001). In moisture-damaged buildings, the symptoms are often considered as irritation or inflammation symptoms because IgE-mediated mould allergy is only seldom found.…”
Section: Introductionmentioning
confidence: 98%